2014
DOI: 10.5551/jat.19265
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Statin Type and Responsiveness to Clopidogrel in Patients Treated with Percutaneous Coronary Intervention: A Subgroup Analysis of the CILON-T Trial

Abstract: Aim:To compare the responsiveness to clopidogrel in patients who were prescribed two different types of statins, atorvastatin vs. rosuvastatin, following percutaneous coronary intervention. Methods: A total of 915 patients were randomized according to the antiplatelet therapy strategy in the CILON-T trial. In this subgroup analysis, we included patients who took atorvastatin (20 mg/day, n = 295) or rosuvastatin (10 mg/day, n = 261) during the entire study period and underwent measurement of the P2Y12 reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…We also detected the interaction between statin and clopidogrel on the aspect of lipid levels, and no statistic influence on lipids level was observed, except for TG level. Four randomized and placebo-controlled trials [20, 25, 38, 39] compared lipid variables in LDL-C and HDL-C between atorvastatin and rosuvastatin and no differences were found. Serebruany et al general described that TC levels were lower in patients treated with a statin than in those receiving no statin [10].…”
Section: Discussionmentioning
confidence: 99%
“…We also detected the interaction between statin and clopidogrel on the aspect of lipid levels, and no statistic influence on lipids level was observed, except for TG level. Four randomized and placebo-controlled trials [20, 25, 38, 39] compared lipid variables in LDL-C and HDL-C between atorvastatin and rosuvastatin and no differences were found. Serebruany et al general described that TC levels were lower in patients treated with a statin than in those receiving no statin [10].…”
Section: Discussionmentioning
confidence: 99%
“…Also, lower exposure to the active metabolite is observed when CYP2C19-metabolized PPIs, most notably omeprazole and esomeprazole, are co-administered with clopidogrel [ 18 ]. Other drugs, such as rosuvastatin, might have an influence on the higher on-treatment platelet reactivity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a few observational studies found that clopidogrel increased adverse cardiac events in patients with a coronary artery stent and coadministered atorvastatin or simvastatin compared with rosuvastatin or pravastatin . However, in other clinical studies, there was a nonsignificant interaction between atorvastatin or simvastatin and clopidogrel, and evidence was not consistent that coadministering CYP3A4‐metabolized statins with clopidogrel increased the frequency of adverse events . Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the possibility of drug–drug interactions (DDIs) between clopidogrel and these drugs has attracted increasing interest. However, these early studies were followed by many other clinical trials and observational studies showing conflicting results …”
mentioning
confidence: 99%